He Who Enters the Bath-House Utters Two Blessings: On the Evolvement and Decline of an Ancient Jewish Prayer - Shemesh, Avraham Ofir (Religions, 2017)
One of the improvements introduced by the Romans was the public bath-house. This article discusses the formation of Jewish prayers, which were composed during the early rabbinic period, following the dangers of the public baths. Sages from late antiquity published two prayers: Before entering to the bathhouse, the bather has to pray for his safety, and after leaving the bath-house he has to thank Gd for not having suffered harm. The dangers of the bathhouse were deemed to include: Weakness, fainting or dehydration due to the heat of the bathhouse; Legs injury of the bathers due to the heat of the warm floor; Dental damage; Sliding on the wet floor; Fear of death due to collapse of the hypocaust. Due to changes in the bath-house in the modern era; these prayers lost their relevance up to a point; or at any rate; they were no longer prescribed or recorded in practice. Bathhouse heaters were no longer located in the hypocaust; and were rather only located close to the wall of the upper room. Hence; falling into the hot lower space was irrelevant. Following the introduction of domestic baths; these prayers have completely vanished.